The Influence of Madrasah Principal Leadership and Teacher Performance on the Quality of Education - Muhammad Irsyad; Zulfani Sesmiarni; Nunu Burhanuddin; Supriadi (IAIN KENDARI, 2026)
The background of this research problem is about the influence of school principal's leadership and teacher's performance on the quality of education, which is closely related to the role of school principals and teachers in managing educational institutions to become quality, developing, and desired by the community. The performance of madrasah teachers depends on how much the Madrasah Head contributes in influencing the behavior of teachers when performing their duties. Has explained that the improvement of school quality is very dependent on the synergy between teachers and school principals. This research uses a quantitative approach using the product moment correlation method. The results show that the regression equation for principal leadership is Y = 68.08 + 0.257X₁, meaning that if the Principal's leadership score is increased by 1 unit, the quality of education increases by 0.257 units. Teacher performance has a positive and significant effect, with regression equation Y = 68.08 + 0.502X₂, indicating that if the Teacher's performance score is increased by 1 unit, the quality of education increases by 0.502 units. Simultaneously, both variables together influence educational quality with the equation Y = 89.17 + 0.257X₁ + 0.531X₂. This study provides information about improving education management in Private Madrasah Tsanawiyah and Private Madrasah Aliyah at Pondok Pesantren Madrasah Tarbiyah Islamiyah Canduang